Penerapan Disiplin Kerja Pegawai di Kantor Desa Boboh Kecamatan Menganti Kabupaten Gresik - Novita Anggreini; Agus Prastyawan (Perspektif Administrasi Publik dan hukum, 2026)
Work discipline is one of the key factors in supporting the effectiveness of village governance and the quality of services provided to the community. This study was motivated by the ongoing issue of employee discipline, particularly regarding adherence to working hours at the Boboh Village Office in Menganti Subdistrict, Gresik Regency. The study aims to analyze the implementation of employee work discipline based on Hasibuan’s indicators, including efforts made to improve work discipline. The study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation, and were subsequently analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results of the study indicate that the implementation of work discipline among employees at the Boboh Village Office has generally been effective. Task assignments have been tailored to employees’ capabilities; leaders set a good example; non-material rewards are provided to maintain work motivation; rules are enforced fairly; supervision and guidance are carried out continuously; and working relationships among employees are harmonious. Nevertheless, instances of tardiness still occur under certain circumstances. Efforts to improve discipline are carried out through routine evaluations, attendance monitoring, guidance, issuing warnings, and the implementation of a digital attendance system. Thus, the enforcement of workplace discipline has been going fairly well, but it still requires ongoing commitment and evaluation to ensure that employee discipline and the quality of service to the public continue to improve.